2019
DOI: 10.1124/jpet.119.261149
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of the Novel Antiepileptic Drug Candidate Padsevonil: Interactions with Synaptic Vesicle 2 Proteins and the GABAA Receptor

Abstract: Padsevonil is an antiepileptic drug (AED) candidate synthesized in a medicinal chemistry program initiated to rationally design compounds with high affinity for synaptic vesicle 2 (SV2) proteins and low-to-moderate affinity for the benzodiazepine binding site on GABA A receptors. The pharmacological profile of padsevonil was characterized in binding and electrophysiological experiments. At recombinant SV2 proteins, padsevonil's affinity for SV2A was greater than that of levetiracetam and brivaracetam (pKi 8.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…2 Furthermore, unlike LEV and BRV, the interaction between Padsevonil and SV2A is not affected by UCB1244283, a positive allosteric modulator of SV2A, suggesting a different binding site for Padsevonil in the SV2A protein. [2][3][4] At recombinant GABA A Rs, Padsevonil displayed low-to-moderate affinity (pKi 6.4) for the benzodiazepine (BZD) binding site. This binding profile has been confirmed in receptor occupancy studies in vivo (mice), where Padsevonil exhibited SV2A occupancy at low doses (median effective dose [ED 50 ] 0.2 mg/kg), and BZD site occupancy at higher doses (ED 50 36 mg/kg).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…2 Furthermore, unlike LEV and BRV, the interaction between Padsevonil and SV2A is not affected by UCB1244283, a positive allosteric modulator of SV2A, suggesting a different binding site for Padsevonil in the SV2A protein. [2][3][4] At recombinant GABA A Rs, Padsevonil displayed low-to-moderate affinity (pKi 6.4) for the benzodiazepine (BZD) binding site. This binding profile has been confirmed in receptor occupancy studies in vivo (mice), where Padsevonil exhibited SV2A occupancy at low doses (median effective dose [ED 50 ] 0.2 mg/kg), and BZD site occupancy at higher doses (ED 50 36 mg/kg).…”
Section: Introductionmentioning
confidence: 96%
“…The selective interaction of Padsevonil with its molecular targets, as intended in the rational drug discovery program, has been confirmed in both in vitro and in vivo studies. 2 Specifically, Padsevonil was designed to bind to the presynaptic SV2 proteins with high affinity and to postsynaptic GABA A Rs, with low-to-moderate affinity. In radioligand displacement studies, Padsevonil has been shown to bind to SV2A with nanomolar affinity (pKi 8.5) that is approximately 100-and 2000-fold greater than that of brivaracetam (BRV) and LEV, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations